Prevalence and anatomic site of Crassicauda sp. infection, and its use in species identification, in kogiid whales from the mid‐Atlantic United States. Issue 3 (7th February 2016) - Keenan‐Bateman, Tiffany F.; McLellan, William A.; Harms, Craig A.; Piscitelli, Marina A.; Barco, Susan G.; Thayer, Victoria G.; Lovewell, Gretchen N.; Clark, Karen L.; Doshkov, Paul K.; Rotstein, David S.; Potter, Charles W.; Pabst, D. Ann
Abstract: The parasitic nematode Crassicauda sp. was initially described in kogiid whales from specimens collected within cervical tissues, uncommon sites of infection for this parasite. Crassicauda sp. has only been reported in Kogia breviceps to date, but no study has yet investigated a large sample of both kogiid species. A 15 yr record of 104 kogiid strandings ( K. sima, n = 40; K. breviceps, n = 64) in North Carolina and Virginia, U.S.A. was used to determine the prevalence of Crassicauda sp. across species, within species across sex, and within sex across length and life history categories. Crassicauda sp. was confirmed to be a species‐specific parasite among kogiids infecting only K. breviceps (prevalence = 45%). Within K. breviceps, prevalence was similar (45%) in both immature and mature males, but increased from 10% in immature to 76% in mature females. This study confirmed the cervico‐thoracic distribution of the parasite, and identified a novel site of infection in a previously undescribed exocrine gland associated with the pigmented "false gill slit." The species‐specific nature of Crassicauda sp. infection, the exocrine gland, and the distinct features of the false gill slit pigmentation associated with the gland, are all useful characters to identify kogiid species in the field.